“Going with the flow” in modeling fibrinolysis - Whyte, Claire S.; Mutch, Nicola J. (Frontiers in Cardiovascular Medicine, 2022)
The formation of thrombi is shaped by intravascular shear stress, influencing both fibrin architecture and the cellular composition which has downstream implications in terms of stability against mechanical and fibrinolytic forces. There have been many advancements in the development of models that incorporate flow rates akin to those found in vivo. Both thrombus formation and breakdown are simultaneous processes, the balance of which dictates the size, persistence and resolution of thrombi. Therefore, there is a requirement to have models which mimic the physiological shear experienced within the vasculature which in turn influences the fibrinolytic degradation of the thrombus. Here, we discuss various assays for fibrinolysis and importantly the development of novel models that incorporate physiological shear rates. These models are essential tools to untangle the molecular and cellular processes which govern fibrinolysis and can recreate the conditions within normal and diseased vessels to determine how these processes become perturbed in a pathophysiological setting. They also have utility to assess novel drug targets and antithrombotic drugs that influence thrombus stability.